1993
DOI: 10.1017/s0252921100029122
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Variations in Intergranular Space

Abstract: Spectrograms of high spatial resolution taken every 15s reveal rapid variations of the continuum intensity and line width. Variations of the latter seem to be related to Doppler velocity gradients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 1 publication
12
42
2
Order By: Relevance
“…This agrees well with the findings obtained from high-resolution spectra that in active regions the granular velocity shifts almost disappear, but that the lines are somewhat broadened (e.g. Nesis et al 1993). Also, we find that the continuum brightness and contrast are in reasonable agreement with the observations only if lines formed deep in the atmosphere, such as the C i lines, are included.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This agrees well with the findings obtained from high-resolution spectra that in active regions the granular velocity shifts almost disappear, but that the lines are somewhat broadened (e.g. Nesis et al 1993). Also, we find that the continuum brightness and contrast are in reasonable agreement with the observations only if lines formed deep in the atmosphere, such as the C i lines, are included.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the turbulent velocities are larger in the active region granules (cf. Nesis et al 1993). This correspondence between the properties of the convective cells returned by the inversion and those of abnormal granulation is close (e.g.…”
Section: For Details)mentioning
confidence: 99%
“…They showed that, at disk center, both, horizontal gradients in the vertical and horizontal velocity at the full resolution are able to reproduce the broadened line profiles after smearing. They concluded that the broadened profiles observed in the dark lanes by Nesis et al (1992) were not necessarily an indication of supersonic flows, whereas the observations in Nesis et al (1993) of line broadened profiles at the edges of granules, between the granule and the intergranular lane, were more likely due to turbulence caused by supersonic flows. Keller (2006) suggested a simple mechanism able to produce broadened line profiles at the edge of granules with no additional turbulence needed.…”
Section: Line Asymmetries and Shiftsmentioning
confidence: 99%
“…Therefore Nesis et al (1993) proposed to use line broadening as an indirect indicator of such flows. However, Solanki et al (1996) compared the velocity field in 2D granulation simulations with synthesized line profiles and showed that, at disk center, other properties of the downflow lanes can cause comparable line broadening, and pointed out that unresolved vertical velocity gradients can also produce apparent line broadening.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation